2017
DOI: 10.3389/fnhum.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

Primary Motor Cortex Activation during Action Observation of Tasks at Different Video Speeds Is Dependent on Movement Task and Muscle Properties

Abstract: The aim of the present study was to investigate how the video speed of observed action affects the excitability of the primary motor cortex (M1), as assessed by the size of motor-evoked potentials (MEPs) induced by transcranial magnetic stimulation (TMS). Twelve healthy subjects observed a video clip of a person catching a ball (Experiment 1: rapid movement) and another 12 healthy subjects observed a video clip of a person reaching to lift a ball (Experiment 2: slow movement task). We played each video at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 60 publications
(71 reference statements)
1
17
4
Order By: Relevance
“…Similarly, other previous studies suggested that the excitability of M1 during passive observation was not modulated in high-speed video playback conditions ( Wrightson et al, 2016 ; Moriuchi et al, 2017 ). As per our previous study ( Moriuchi et al, 2014 , 2017 ), we hypothesized that M1 excitability during action observation would be influenced by activation of the PMv and IPL, as constituents of the AON, which are dynamically modulated depending on whether the element of movement is recognized or not. Because subjects were able to recognize movement elements easily, our findings indicate that the modulation of M1 excitability may not be detectable or present during the observation of videos of simple movement tasks, such as repetitive finger abduction, played at different playback speeds.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similarly, other previous studies suggested that the excitability of M1 during passive observation was not modulated in high-speed video playback conditions ( Wrightson et al, 2016 ; Moriuchi et al, 2017 ). As per our previous study ( Moriuchi et al, 2014 , 2017 ), we hypothesized that M1 excitability during action observation would be influenced by activation of the PMv and IPL, as constituents of the AON, which are dynamically modulated depending on whether the element of movement is recognized or not. Because subjects were able to recognize movement elements easily, our findings indicate that the modulation of M1 excitability may not be detectable or present during the observation of videos of simple movement tasks, such as repetitive finger abduction, played at different playback speeds.…”
Section: Discussionsupporting
confidence: 77%
“…A previous study comparing differences in the effects of manipulating the speed of a viewed task (i.e., video speed condition) revealed that M1 excitability during passive observation was only increased when observing a rapid movement on a video played back slowly, but not when it was played at normal or fast speeds ( Moriuchi et al, 2014 , 2017 ), indicating that M1 excitability was only altered when the element of movement could be easily recognized. Similarly, other previous studies suggested that the excitability of M1 during passive observation was not modulated in high-speed video playback conditions ( Wrightson et al, 2016 ; Moriuchi et al, 2017 ). As per our previous study ( Moriuchi et al, 2014 , 2017 ), we hypothesized that M1 excitability during action observation would be influenced by activation of the PMv and IPL, as constituents of the AON, which are dynamically modulated depending on whether the element of movement is recognized or not.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the excitability of the M1 was higher when the observed action was at low-speed replays (half and quarter speeds) than at normal-speed replays. More recently, Moriuchi et al (2017) reported that the same effects were confirmed only when viewing the low-speed replay video of rapid movements (i.e., catching a ball); such effects were not confirmed when viewing slow movements (i.e., reaching for and lifting a ball). The authors explained that the benefit of using slow-motion footage is likely to be obtained only for rapid movements, in which the components of observed actions would not be visible at normal speed.…”
Section: Introductionmentioning
confidence: 97%
“…Slow-motion footage of sports actions is widely used as a visual learning tool in observing complex and quick motor behaviors by athletes, such as a golfer’s swing movement and a tennis player’s forehand stroke ( Williams et al, 2002 ; Wilson, 2008 ). Recent studies ( Moriuchi et al, 2014 ; Moriuchi et al, 2017 ) on action observation have reported that extension of the observation time in slow-motion footage provides benefits of understanding the intention of an opponent’s action, at least when observing rapid movements. Moriuchi et al (2014) examined how speeds of observed actions affected the excitability of the primary motor cortex (M1).…”
Section: Introductionmentioning
confidence: 99%